A Comparison Between the Food Ratio Poverty Line and the Leyden Poverty Line - van Praag, Bernard M. S.; Spit, Jan S.; van de Stadt, Huib (The Review of Economics and Statistics, 1982)
Bernard M. S. van Praag, Jan S. Spit, Huib van de Stadt, A Comparison Between the Food Ratio Poverty Line and the Leyden Poverty Line, The Review of Economics and Statistics, Vol. 64, No. 4 (Nov., 1982), pp. 691-694